Strategi Pengembangan Ekonomi Lokal melalui Koperasi Multipihak - Ahmad Subagyo; Diah Nofitasari; Sugianto Ikhsan; Muhammad Fahreza (Bandung Conference Series: Economics Studies, 2024)
Abstract. Local economic development is an important effort in strengthening the economy of a region. Multi-stakeholder cooperatives, which involve various stakeholders, have a strategic role in encouraging local economic development through community empowerment and the development of micro, small, and medium enterprises (MSMEs). This study aims to analyze the role of multi-stakeholder cooperatives in local economic development in Tomo District, Sumedang Regency, and to formulate relevant and effective strategies to overcome the main problems faced by local MSMEs, such as capital, marketing, and product packaging. This case study uses a SWOT analysis approach to identify internal factors (strengths and weaknesses) and external factors (opportunities and threats) related to the establishment of multi-stakeholder cooperatives in Tomo District. Data analysis was carried out by comparing internal and external factors, and compiling a SWOT matrix to formulate alternative strategies. The results of the study indicate that multi-stakeholder cooperatives have great potential in supporting local economic development in Tomo District. However, there are challenges such as limited capital, lack of community knowledge about cooperative management, limited marketing infrastructure, and low technological capabilities among MSME actors. Based on the SWOT analysis, this study recommends a strategy for establishing multi-party cooperatives involving various parties, increasing human resource capacity, easier access to financing, developing downstream businesses, digital marketing, and partnerships with various parties. The implementation of this strategy is expected to increase the competitiveness and sustainability of MSMEs in Tomo District, as well as encourage inclusive and sustainable local economic development. Abstrak. Pengembangan ekonomi lokal merupakan upaya penting dalam memperkuat perekonomian suatu daerah. Koperasi multipihak, yang melibatkan berbagai pemangku kepentingan, memiliki peran strategis dalam mendorong pembangunan ekonomi lokal melalui pemberdayaan masyarakat dan pengembangan usaha mikro, kecil, dan menengah (UMKM). Penelitian ini bertujuan untuk menganalisis peran koperasi multipihak dalam pengembangan ekonomi lokal di Kecamatan Tomo, Kabupaten Sumedang, serta merumuskan strategi yang relevan dan efektif untuk mengatasi permasalahan utama yang dihadapi UMKM setempat, seperti permodalan, pemasaran, dan pengemasan produk. Studi kasus ini menggunakan pendekatan analisis SWOT untuk mengidentifikasi faktor internal (kekuatan dan kelemahan) serta faktor eksternal (peluang dan ancaman) terkait pendirian koperasi multipihak di Kecamatan Tomo. Analisis data dilakukan dengan membandingkan faktor internal dan eksternal, serta menyusun matriks SWOT untuk merumuskan alternatif strategi. Hasil penelitian menunjukkan bahwa koperasi multipihak memiliki potensi besar dalam mendukung pengembangan ekonomi lokal di Kecamatan Tomo. Namun, terdapat tantangan seperti keterbatasan modal, kurangnya pengetahuan masyarakat tentang manajemen koperasi, infrastruktur pemasaran yang terbatas, dan rendahnya kemampuan teknologi di kalangan pelaku UMKM. Berdasarkan analisis SWOT, penelitian ini merekomendasikan strategi pendirian koperasi multipihak yang melibatkan berbagai pihak, peningkatan kapasitas sumber daya manusia, akses pembiayaan yang lebih mudah, pengembangan usaha hilir, pemasaran digital, dan kemitraan dengan berbagai pihak. Implementasi strategi ini diharapkan dapat meningkatkan daya saing dan keberlanjutan UMKM di Kecamatan Tomo, serta mendorong pembangunan ekonomi lokal yang inklusif dan berkelanjutan.